Does Structural Power Matter? Board Attributes and Firm Performance: Moderated by CEO Duality - Korir, Fiona Jepkosgei; Tenai, Joel K (SEISENSE Journal of Management, 2020)
Purpose- The study investigates the moderating role of Chief Executive Officer Duality onboard attributes and firm performance of companies listed in Kenya. Design/Methodology- The research used a longitudinal research design. Panel data were derived from published accounts for sixteen years that is from 2002-2017. IGLS regression models were used to test the hypothesis. Findings- The empirical results indicated that the independence of the board, the size of the board, and the duration in which the board member served the organization positively influence the firm performance. However, CEO duality does not moderate the relationship. Practical Implications- Regulatory bodies such as NSE and CMA in Kenya should ensure that listed firms have more independent directors serving a board, ensure a reasonable size of the board and increase the board tenure to enhance firm performance. Further, the combined roles of the CEO and chairman may not influence the efficiency of the board in the Kenyan context.